Creative problem-solving ability does not occur by chance: Examining the dynamic system model of creative problem solving ability. (May 2023) - Lin, Chia-Yi
This study examined Cho's dynamic system model of creative problem-solving ability in a sample of 112 gifted and non-gifted students. The cluster analysis and t-test results indicated that students should be categorized into high and low performance groups. Students who scored three points or more across all attributes also had a higher likelihood of possessing better mathematical creative problem-solving abilities. Furthermore, significant differences were found in the two groups' scores on the Creative Problem Solving Attributes Inventory and Mathematical Creative Problem Solving Ability Test. The environment attribute was the only one on which the two groups did not differ significantly; this may be the result of education fever in Asian societies. Finally, the results of this study not only indicated that creativity does not rely on a single factor but that a well-balanced environment is imperative to nurturing creativity.